Incidental iron oxide nanoclusters drive confined Fenton-like detoxification of solid wastes towards sustainable resource recovery - Zhichao Yang; Yuyang Yin; Mengyuan Liang; Wanyi Fu; Jiahe Zhang; Fangzhou Liu; Wen Zhang; Bingcai Pan (Nature Communications)
Abstract The unique properties of nanomaterials offer vast opportunities to advance sustainable processes. Incidental nanoparticles (INPs) represent a significant part of nanomaterials, yet their potential for sustainable applications remains largely untapped. Herein, we developed a simple strategy to harness INPs to upgrade the waste-to-resource paradigm, significantly reducing the energy consumption and greenhouse gas emissions. Using the recycling of fly ash from municipal solid waste incineration (MSWI) as a proof of concept, we reveal that incidental iron oxide nanoclusters confined inside the residual carbon trigger Fenton-like catalysis by contacting H2O2 at circumneutral pH (5.0–7.0). This approach efficiently detoxifies the adsorbed dioxins under ambient conditions, which otherwise relies on energy-intensive thermal methods in the developed recovery paradigms. Collective evidence underlines that the uniform distribution of iron oxide nanoclusters within dioxin-enriched nanopores enhances the collision between the generated active oxidants and dioxins, resulting in a substantially higher detoxification efficiency than the Fe(II)-induced bulk Fenton reaction. Efficient and cost-effective detoxification of MSWI fly ash at 278‒288 K at pilot scale, combined with the satisfactory removal of adsorbed chemicals in other solid wastes unlocks the great potential of incidental nanoparticles in upgrading the process of solid waste utilization and other sustainable applications.